Intestinal cystic pneumatosis: a rare entity - Guzmán-Argüello, Gloria; Silva-Zamora, Jorge; Salgado-Adame, Israel (International Journal of Research in Medical Sciences, 2022)
Pneumatosis intestinalis is the presence of gas within the wall of the gastrointestinal tract. The gas forms bubbles containing nitrogen, hydrogen and carbon dioxide in most cases is intramural. Many factors are associated with this entity such as bacterial gas production (Clostridium difficile), increased intraluminal pressure (vomiting), mucosal injury (inflammatory bowel disease and immunosuppression), pulmonary gas (pulmonary obstruction and chronic cough) and combination of factors. The most frequent symptom is abdominal pain however physical examination is not very helpful in the diagnosis, the reason why computed tomography is the best imaging modality for this disease. The treatment depends in the underlying cause and is debated.